Penerapan Model Pembelajaran Round Club Untuk Meningkatkan Keaktifan Dan Hasil Belajar Siswa - Adiyatma; Nur Rohman; Hendra SH (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to determine the application of the Round Club learning model in increasing student activities in Grade IV of MIN 3 West Aceh. The approach used in this study is qualitative, specifically Classroom Action Research (CAR). The subjects in this study were 18 students in grade IV of MIN 3 West Aceh. The data collection techniques used are observation and testing techniques. The results showed that in pre-action, only 4 students, or 22.2% completed their learning results with an average score of 54.4. The test result data for cycle I showed that students who obtained a score of > 70 were 9 or 50% students with an average score of 66.4, while the test result data from cycle II showed that students who obtained a score of > 70 were 15 students or 83.3% with an average score of 76.1. The results of observation of student activities in the first cycle as many as 73.1% were in the good category, while in the second cycle reached 80.8% in the very good category.